Active surveillance of early onset disease due to group B streptococci in newborns - Straková, L; Motlová, J (The Indian journal of medical research, 2004)
BACKGROUND & OBJECTIVES: Early onset disease (EOD) due to group B streptococci (GBS) poses a serious threat in many countries. In the Czech Republic neither summarized data on the EOD incidence are available nor a nationwide prevention program has been initiated. The present surveillance was initiated to establish the incidence of EOD due to GBS in newborns in the Czech Republic, distribution of GBS serotypes and GBS susceptibility to antimicrobials. METHODS: Both invasive and carrier GBS isolates from newborns and the data on the newborns' clinical status and maternal colonization and intrapartum prophylaxis were collected from 30 microbiological and clinical centres all over the Czech Republic within prospective active surveillance. HCl extracts of the GBS strains were precipitated with rabbit polysaccharide (I-VIII) and protein (c,R) antisera. RESULTS: Between January 2001 and September 2002, GBS isolates from 239 full-term and 46 preterm newborns were collected. Of the 285 GBS positive newborns, 105 had invasive EOD, 42 showed suspected EOD, and in 56 clinical diagnosis was not specified. Eighty two GBS isolates were obtained from healthy colonized infants. The isolates obtained from newborns with confirmed invasive EOD were mostly of serotype III (42%), followed by serotypes V a Ia (13% each). Types Ia (26%), III (22%) and II (20%) were most frequent among the isolates from colonized individuals. Protein antigens (c protein, R protein) either coupled with polysaccharide or alone were found in 70 per cent (30 and 40 %, respectively) of the study isolates. INTERPRETATION & CONCLUSION: The incidence of EOD due to GBS found in the Czech Republic 0.7-1.0 per 1000 live births was comparable with the rates reported in the countries where the prevention programme has been implemented nationwide. Serotypes III, V and Ia prevailing among the isolates from Czech newborns with EOD belonged to those most frequently identified in the USA and Western European countries.
Keywords: streptokokové infekce; novorozenec; Infant, Newborn; Streptococcal Infections; přenašečství; Carrier State; Humans; Česká republika; Acute Disease; lidé; Streptococcus agalactiae; akutní nemoc; Czech Republic